Penerapan Digitalisasi UMKM melalui E-Commerce dan Portal Informasi sebagai Strategi Pemasaran Produk - Muhardono, Ari; Mahmudah, Dina Amalia; Tsamara, Tsamara; Baqo, Muhammad (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This research is a research and development research that aims to design UMKM digitization, which is to help SMEs ATBM in Cepagan Village increase marketing reach through E-Commerce and Information Portals. The System Development method used is the Prototype Method using an approach to make a design quickly and gradually which includes requirements analysis, building prototyping, evaluating prototyping, coding the system, testing the system, and evaluating the system. The results of this research are the implementation of the digitization of MSMEs which includes the creation of E-Commerce, Information Portal Websites, QRIS Digital Payment Methods, and Application of Search Engine Optimization. With the existence of E-Commerce, it can help MSMEs in reaching a wider market and increasing product sales turnover, the information portal website for the ATBM Weaving Village in Cepagan Village is used as a medium of information about the activities of the ATBM Weaving Village in Cepagan Village with the aim of reviving the image and existence of Cepagan Village. known as the "Kampung Tenun" Cepagan Village so that it is known to the wider community and has proven to be effective in increasing website traffic so that the potential for purchases is higher